2008
DOI: 10.1021/ja808243k
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Inorganic Inks for Low-Temperature Fabrication of ZnO TFTs

Abstract: A simple, low-cost, and nontoxic aqueous ink chemistry is described for digital printing of ZnO films. Selective design through controlled precipitation, purification, and dissolution affords an aqueous Zn(OH)(x)(NH(3))(y)((2-x)+) solution that is stable in storage, yet promptly decomposes at temperatures below 150 degrees C to form wurtzite ZnO. Dense, high-quality, polycrystalline ZnO films are deposited by ink-jet printing and spin-coating, and film structure is elucidated via X-ray diffraction and electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
296
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(305 citation statements)
references
References 42 publications
5
296
1
Order By: Relevance
“…There are two main reasons for the high rectification ratios achieved in our coplanar ZnO Schottky diodes [ Figure 1(c)]. Firstly, the quality of the ZnO layers processed from the carbonfree Zn(OH)x(NH3)y (2-x)+ precursor solutions appear to be excellent exhibiting high electron mobility (10 cm 2 /Vs) due to their continuous polycrystalline nature 5,18,40 . Secondly, the coplanar asymmetric Au/Al electrodes architecture employed is rather unique and can be realized at such scale only via a-Lith.…”
Section: Methodsmentioning
confidence: 99%
“…There are two main reasons for the high rectification ratios achieved in our coplanar ZnO Schottky diodes [ Figure 1(c)]. Firstly, the quality of the ZnO layers processed from the carbonfree Zn(OH)x(NH3)y (2-x)+ precursor solutions appear to be excellent exhibiting high electron mobility (10 cm 2 /Vs) due to their continuous polycrystalline nature 5,18,40 . Secondly, the coplanar asymmetric Au/Al electrodes architecture employed is rather unique and can be realized at such scale only via a-Lith.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] A few studies on low-temperatureprocessable MOSs have been reported. [13][14][15][16] However, the authors of these studies used either complex and unstable precursors that required significant effort and multiple steps for synthesis or complicated chemical reactions that are not appropriate for the general fabrication technique. Although methods based on nanostructures, nanoparticles, nanorods or carbon-related materials also allow low-temperature deposition, concerns about the uniformity of the resulting devices related to the uncontrollable distribution of nanosized materials still remain.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, by using ITO source/drain electrodes, they were able to improve the device performances, with a mobility of 7.6 cm 2 /Vs and on-off ration of 10 7 . In an effort to lower down the processing temperature, Meyers et al 46 reported the design and synthesis of an ink based on zinc complex ions, Zn(OH) x (NH 3 ) y (2-x)+ in water and isopropanol solution. A modified HP thermal inkjet printer was used for their study.…”
Section: Development Of Printed Metal Oxide Tftsmentioning
confidence: 99%
“…19 In 2 O 3 Rheology 10.2 10 5 V on = 0 Lee et al 22 SnO 2 Thermal inkjet 3.62 10 3 V on = −39 Lee et al 23 IZTO Piezoelectric inkjet 30 10 6 V on = 2 Han et al 24 IGO Piezoelectric inkjet 5.5 10 5 V on = −21 Kim et al 25 ZTO Piezoelectric inkjet 4.98 10 9 V on = −9 Avis et al 28 IZTO Piezoelectric inkjet 114. 8 10 7 V th = −0.16 Garlapati et al 29 In 2 O 3 Piezoelectric inkjet 126 * 2 × 10 7 V on = 0.37 Kim et al 31 ZTO Piezoelectric inkjet 0.58 5 × 10 6 V th = 1.9 Jeong et al 32 ZTO Piezoelectric inkjet 0.58 10 7 V th = 1.7 Kim et al 33 IGZO Piezoelectric inkjet 0.03 5 × 10 4 V th = 6.2 Kim et al 34 IGZO Piezoelectric inkjet 0.055 10 3 V th = −0.5 Wang et al 35 IGZO Piezoelectric inkjet 1.41 4 × 10 7 V th = −0.5 Wang et al 36 IGZO Piezoelectric inkjet 0.82 6 × 10 5 V th = 7 Hennek 37 IGZO Piezoelectric inkjet 2.45 9 × 10 5 V th = 21.9 Jeong et al 38 IGZO Piezoelectric inkjet 7.6 10 7 V th = 11.1 Meyers et al 39 ZnO Thermal inkjet 6.1 >10 6 V on = −7 Dilfer et al 40 IZO Flexographic 2.4 5 × 10 7 V th = 4 Choi et al 41 IGZO Gravure 0.81 10 6 V on = 1.35 Eun et al 42 ZnO Transfer 0.49 * * 10 5 V th = 12 Lee et al 43 IZO EHD 32 * * * 10 3 V th = <2 Lee et al 44 ZTO EHD 9.82 3 × 10 6 V th = 2.16 Jeong et al 45 IGZO EHD 10.4 10 7 V th = 4.1 Dasgupta et al 46 In 2 O 3 Piezoelectric inkjet 0.8 * * * * 2 × 10 3 V on = 0 Liu et al 47 ZnO Piezoelectric inkjet 0.69 4 × 10 1 V th = 25.5 Noh et al 48 ZnO NW SAP 4 10 4 EHD: Electrohydrodynamic SAP: Self-aligned inkjet printing * The device was performed with polymer dielectric layer * * The performances were measured from the device prior to the transferring * * * The device was performed with HfO dielectric layer * * * * The device was fabricated at room temperature…”
Section: Summary and Future Directionsmentioning
confidence: 99%